Information-sharing ethical dilemmas and decision-making for public health nurses in Japan. (August 2015) - Suzuki, Chisato; Ota, Katsumasa; Matsuda, Masami
Background: Information sharing is one of the most important means of public health nurses collaborating with other healthcare professionals and community members. There are complicated ethical issues in the process. Research objectives: To describe the ethical dilemmas associated with client information sharing that Japanese public health nurses experience in daily practice and to clarify their decision-making process to resolve these dilemmas. Research design: Data were collected using a three-phase consensus method consisting of semi-structured interviews, self-administered questionnaires and a group interview. Participants and research context: We surveyed administrative public health nurses in Shizuoka Prefecture, Japan. The semi-structured interviews were carried out with 12 administrative public health nurses, and the self-administered questionnaires were sent to all 899 administrative public health nurses. The group interview was carried out with eight administrative public health nurses. Ethical considerations: Ethical approval was granted by the ethics committee of the School of Health Sciences, Nagoya University, Japan (8-158, 9-130). Findings: Information-sharing ethical dilemmas occurred most often when clients' decisions did not coincide with the nurses' own professional assessments, particularly when they faced clinical issues that were inherently ambiguous. In their decision-making processes, nurses prioritised 'protection of health and life'. Discussion: These findings suggest that, above all, they sought to address urgent risks to clients' lives while upholding the principle of client autonomy as much as possible. In such cases, the nurses made decisions regarding whether to share information about the client depending on the individual situation. Conclusion: Public health nurses should protect the client's health while taking into consideration their relationship with the client.